Adapting the 15-minute city model in Cairo: mobility challenges and opportunities - Omar, Meral; Ashour, Mohamed Ayman; Serag, Yehya; Elshater, Abeer (Journal of Architecture and Urbanism, 2025)
The 15-minute city model, a visionary approach to urban planning, envisions neighbourhoods where residents can access all essential daily needs – work, education, healthcare, shopping, and leisure –within a 15-minute walk or bike ride. This study assesses the challenges and opportunities of implementing the 15-minute city model in Downtown Cairo, Egypt. The study examines the current state of public spaces, transportation, and walkability in the area through ethnographic research, including extensive field observations and frequent attendance at design workshops with developers, as well as numerous site visits and in-depth semi-structured interviews with diverse stakeholders. Stakeholders included the developer of the Cairo House project, the Cairo Bike project manager, urban researchers, tourists, residents and business owners within the study area. Data were analysed using thematic coding to identify recurring patterns and conflicting perspectives. The findings reveal significant challenges, including traffic congestion, limited public spaces, and inadequate pedestrian and cycling infrastructure. The study explores potential solutions, including enhancing public transportation, creating safe and accessible environments for pedestrians and cyclists, promoting mixed-use development, and developing vibrant and accessible public spaces. The main findings underscore the significance of community engagement and participatory planning in ensuring the successful and equitable implementation of the 15-minute city model within this unique and historic urban context.